Application of a Catalytic Asymmetric Povarov Reaction using Chiral Ureas to the Synthesis of a Tetrahyroquinoline Library - Gerard, Baudouin (2012)
[Image: see text] A 2328-membered library of 2,3,4-trisubstituted tetrahydroquinolines was produced using a combination of solution- and solid-phase synthesis techniques. A tetrahydroquinoline (THQ) scaffold was prepared via an asymmetric Povarov reaction using cooperative catalysis to generate three contiguous stereogenic centers. A matrix of 4 stereoisomers of the THQ scaffold was prepared to enable the development of stereo/structure-activity relationships (SSAR) upon biological testing. A sparse matrix design strategy was employed to select library members to be synthesized with the goal of generating a diverse collection of tetrahydroquinolines with physicochemical properties suitable for downstream discovery.